Overexpression of cyclin D1 and cdk4 in tumorigenesis of sporadic hepatoblastomas - Kim, H; Ham, EK; Kim, YI; Chi, JG; Lee, HS; Park, SH; Jung, YM; Myung, NK; Lee, MJ; Jang, JJ (ELSEVIER SCI IRELAND LTD, 1998)
Abnormality of the cyclin Dl/cdk4/p16INK4a/pRb pathway during tumorigenesis has recently been reported. Hepatoblastoma is a rare malignant liver tumor of childhood, but underlying abnormalities of cell-cycle regulating protein remain to be elucidated. The expression of cyclin D1, cdk4, p16 and retinoblastoma gene product (pRb) was studied by immunohistochemistry in 17 paraffin-embedded tissues consisting of both tumor and corresponding non-neoplastic tissues. Tumor tissues showed overexpression of cyclin D1 (13/17, 76%) and cdk4 (15/17, 88%). Eleven cases showed co-overexpression of both cyclin D1 and cdk4. No abnormal p16 or pRb expression was noted. In the group with a high score (+4) for cyclin D1 expression, a positive correlation with tumor recurrence was noted (P = 0.043). These data suggest that overexpressed cyclin D1 and cdk4 protein might play an important role in the tumorigenesis of hepatoblastoma and that in the group with high cyclin D1 expression, tumor recurrence may be more frequent. (C) 1998 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: FAMILIAL ADENOMATOUS POLYPOSIS; HUMAN HEPATOCELLULAR-CARCINOMA; CHROMOSOME ARM 11P; PROGNOSTIC IMPLICATIONS; HUMAN SARCOMAS; BREAST-CANCER; P53 GENE; CHILDHOOD; TUMORS; AMPLIFICATION